2007
DOI: 10.1002/qj.49
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of subsidence in the hurricane eye

Abstract: Two hurricane eye features that have yet to be adequately explained are the clear-air moat that forms at the outer edge of the eye and the hub cloud that forms near the circulation centre. To investigate whether these features can be explained by the spatial distribution of the subsidence field, we have derived an analytical solution of the Sawyer-Eliassen transverse circulation equation for a three-region approximation with an unforced central eye region of intermediate or high inertial stability, a diabatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 28 publications
10
90
1
Order By: Relevance
“…While not a central theme of this paper, it is interesting to examine the last item above in the light of a recent study by Schubert et al (2007), who showed that the narrow region of subsidence in the eye occurs when the average Rossby length in the eye is less than 0.6 times the eye radius, which they took to be the radius of maximum tangential wind speed, R max . Schubert et al (2007) defined the local Rossby length, L R , in terms of that at large radii, say L RR , which they took to be 1000 km.…”
Section: Azimuthally Averaged Aspectsmentioning
confidence: 99%
“…While not a central theme of this paper, it is interesting to examine the last item above in the light of a recent study by Schubert et al (2007), who showed that the narrow region of subsidence in the eye occurs when the average Rossby length in the eye is less than 0.6 times the eye radius, which they took to be the radius of maximum tangential wind speed, R max . Schubert et al (2007) defined the local Rossby length, L R , in terms of that at large radii, say L RR , which they took to be 1000 km.…”
Section: Azimuthally Averaged Aspectsmentioning
confidence: 99%
“…There are several derivations of the Sawyer-Eliassen equation in the literature (e.g., Shapiro and Willoughby 1982;Schubert et al 2007). In this study we integrate the version derived by Bui et al (2009):…”
Section: B the Sawyer-eliassen Modelmentioning
confidence: 99%
“…These include two-dimensional vortex interactions (Kuo et al 2004(Kuo et al , 2008, anisotropic upscale energy cascades (Terwey and Montgomery 2008), and changes in axisymmetric efficiency [as defined by Schubert and Hack (1982) and Hack and Schubert (1986)] related to the radial expansion of the azimuthally averaged tangential wind field and sustained latent heating outside of the primary eyewall ). Other models propose wave-mean flow interaction associated primarily with vortex Rossby waves and their modification to the storm inner-core region (Montgomery and Kallenbach 1997;Martinez et al 2010a,b;Menelaou et al 2012;Qiu et al 2010;Abarca and Corbosiero 2011) or the generation and accumulation of convectively induced potential vorticity anomalies and the absence of vortex Rossby wave activity (Judt and Chen 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The eye is a region of subsidence and the circulation in it is 'indirect' i.e. warm air is sinking (Smith 1980, Shapiro and Willoughby 1982, Schubert et al 2007). …”
Section: Introductionmentioning
confidence: 99%